Spiritual Intelligence as a Determinant in Understanding Accounting Concepts - Harwinsyah, Guna Baktiar; Gunawan, Hendra (Department of Accounting-Faculty of Economic and Business (FEB), 2024)
Intelligence within oneself as one of the factors that influence the level of success. This study aims to determine the influence of spiritual intelligence on the understanding of accounting concepts. This study uses a quantitative approach and sampling using a purposive sampling technique. The sample in this study were 148 respondents, consisting of active students in Accounting study programs. The analytical tool used is simple regression analysis. The results showed that spiritual intelligence has a positive effect on students' understanding of accounting, meaning the better one's spiritual intelligence, the better the understanding of accounting.